Thermal behavior and smoke characteristics of glass/epoxy laminate and its foam core sandwich composite - Xu, Yanying; Sun, Xiaodong; Shen, Ruiqing; Wang, Zhi; Wang, Qingsheng (Journal of thermal analysis and calorimetry, 2020)
Thermal behavior and smoke characteristics of glass/epoxy laminate and its foam core sandwich composite were comprehensively investigated using thermogravimetric analysis, TG–FTIR analysis, smoke density test and cone calorimeter test. The thermal decomposition, thermal interpretation of gas release, smoke density, smoke release, carbon monoxide and carbon dioxide productions were analyzed and compared for glass/epoxy laminate and its foam core sandwich composite. Their kinetic and thermodynamic models were obtained, and the apparent activation energy, pre-exponential factor and thermodynamic parameters were determined correspondingly. The results show that there are significant differences in the thermal behavior and smoke characteristics between these two composites. Compared with glass/epoxy laminate, foam core sandwich composite demonstrates a higher propensity of pyrolysis and combustions and greater hazards to life and property.